Pengaruh Kinerja Lingkungan Terhadap Corporate Social Responsibility (CSR) Disclosure dan Kinerja Finansial Perusahaan Kimia dan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar dalam BEI tahun - Tito Anindito; Moh. Didik Ardiyanto (Diponegoro Journal of Accounting, 2013)
This research aims to examine the effect of Environmental Performance on Corporate Social Responsibility (CSR) Disclosure and Financial Performance. Environmental Performance is measured using the PROPER (Program Penilaian Peringkat Kinerja Perusahaan dalam Pengelolaan Lingkungan Hidup) which is a program of the Ministry of Environment. Corporate Social Responsibility (CSR) Disclosure was measured using 79 items of GRI. Financial performance is measured using by annual stock return.The data in this research are the chemical companies and the mines listed in the Indonesia Stock Exchange (BEI) in 2007-2010 who participated in the PROPER (Program Penilaian Peringkat Kinerja Perusahaan dalam Pengelolaan Lingkungan Hidup). The type of data used are secondary data, the samples used were 36 chemical and mining companies listed in the Stock Exchange, the sampling method was purposive sampling method. The data analysis method used is multiple linear regression analysis. The data analysis and test of the hypothesis is done by using the SPSS software version 17.The test results indicate that environmental performance has a significant iinfuence Corporate Social Responsibility (CSR) Disclosure. The test result for the second hypothesis indicated that environmental performance has no significant influence the financial performance, and the third hypothesis indicates that Corporate Social Responsibility (CSR) Disclosure has no significant impact influence toward the financial performance. However, this results of the test show that there are an indirect impact that statiscally significant of environmental performance toward financial performance of the company through Corporate Social Responsibility (CSR) Disclosure.